2019
DOI: 10.1128/mbio.02690-18
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus T Antigen InducesAPOBEC3BExpression Using an LXCXE-Dependent and TP53-Independent Mechanism

Abstract: APOBEC3B is a single-stranded DNA cytosine deaminase with beneficial innate antiviral functions. However, misregulated APOBEC3B can also be detrimental by inflicting APOBEC signature C-to-T and C-to-G mutations in genomic DNA of multiple cancer types. Polyomavirus and papillomavirus oncoproteins induce APOBEC3B overexpression, perhaps to their own benefit, but little is known about the cellular mechanisms hijacked by these viruses to do so. Here we investigate the molecular mechanism of APOBEC3B upregulation b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 73 publications
4
44
0
Order By: Relevance
“…Indeed, high risk α-HPVs have been shown to trigger and stabilize A3A and A3B via their oncoproteins E6 and E7 [ 16 , 45 47 ]. Likewise, it has recently been shown that BK and JC β-PyV upregulate A3B through their large T antigen [ 17 , 48 ]. In both the α-HPVs and β-PyVs, the induced A3 proteins are enzymatically active and therefore capable of deamination [ 17 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high risk α-HPVs have been shown to trigger and stabilize A3A and A3B via their oncoproteins E6 and E7 [ 16 , 45 47 ]. Likewise, it has recently been shown that BK and JC β-PyV upregulate A3B through their large T antigen [ 17 , 48 ]. In both the α-HPVs and β-PyVs, the induced A3 proteins are enzymatically active and therefore capable of deamination [ 17 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a role for A3B in cancer mutagenesis and evolvability has been welldocumented, universally accepted genomic substrates have yet to be described. Conflicting studies show A3B can target transcription-associated substrates as well as replication and recombination-associated substrates (18,54,74,95,96). Therefore, it is plausible that A3B-mediated mutagenesis can be exacerbated during G1/S stalling, which may create more exposed ssDNA substrates.…”
Section: Apobec3b and Cdk4mentioning
confidence: 99%
“…Various DNA damaging agents also stimulate A3B expression including hydroxyurea, gemcitabine, aphidicolin, and camptothecin ( Kanu et al, 2016 ; Yamazaki et al, 2020 ). Interestingly, as alluded above, HPV infection induces A3B expression by mechanisms requiring the viral E6 and E7 oncoproteins ( Mori et al, 2015 ; Mori et al, 2017 ; Starrett et al, 2019 ; Verhalen et al, 2016 ; Vieira et al, 2014 ; Warren et al, 2015 ; Westrich et al, 2018 ). E6 appears to induce A3B in part by recruiting the transcription factor TEAD4 to promoter sequences ( Mori et al, 2015 ; Mori et al, 2017 ).…”
Section: Introductionmentioning
confidence: 98%
“…Fourth, A3B expression correlates positively with APOBEC signature mutation loads in breast cancer ( Burns et al, 2013a ), and its overexpression associates with branched evolution in breast and lung cancer ( de Bruin et al, 2014 ; Lee et al, 2019 ; Roper et al, 2019 ). Fifth, A3B expression is induced by human papillomavirus (HPV) and polyomavirus (PyV) infections, which relates to the fact that cervical, head/neck, and bladder cancers have high proportions of APOBEC signature mutations ( Gillison et al, 2019 ; Henderson et al, 2014 ; Starrett et al, 2019 ; Verhalen et al, 2016 ; Vieira et al, 2014 ). Last, A3B overexpression associates with poor clinical outcomes including drug resistance and metastasis ( Glaser et al, 2018 ; Law et al, 2016 ; Serebrenik et al, 2020 ; Sieuwerts et al, 2017 ; Sieuwerts et al, 2014 ; Walker et al, 2015 ; Xu et al, 2015 ; Yamazaki et al, 2019 ; Yan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation